2019
DOI: 10.1002/aet2.10356
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Emergency Medicine Clinical Learning Environment

Abstract: Background: Residencies are grappling with ways to identify methods to internally monitor and improve their learning environments. Building on prior work, the objective of this study was to determine emergency medicine (EM) internal evaluations of perceived organizational support and psychological safety and compare to the results from the Accreditation Council for Graduate Medical Education (ACGME) Resident Survey for the purpose of program improvement and to explore factors affecting residents' perception of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The primary aim of this study was to evaluate the perception of EM residents as it relates to psychological safety and organizational support in their CLEs. Data from our multisite analysis are consistent with the single-site results of Feeser et al, 20 indicating that the CLE within EM residencies is perceived as generally psychologically safe and supportive across multiple sites. This is indicated by aggregate PSS and SPOS scores.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The primary aim of this study was to evaluate the perception of EM residents as it relates to psychological safety and organizational support in their CLEs. Data from our multisite analysis are consistent with the single-site results of Feeser et al, 20 indicating that the CLE within EM residencies is perceived as generally psychologically safe and supportive across multiple sites. This is indicated by aggregate PSS and SPOS scores.…”
Section: Discussionsupporting
confidence: 88%
“…The PSS includes seven questions and the SPOS includes 16 questions, both utilizing Likert‐type scales from “strongly disagree” to “strongly agree.” The PSS is on a 5‐point scale and the SPOS is on a 7‐point scale. Both the PSS and SPOS have previous validity evidence when examining resident perceptions of the CLE 19,20 . Like in the studies by Appelbaum et al 19 .…”
Section: Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…Respondents were asked which country they studied in, and place of study was categorised according to the United Nations (UN) M49 classification of geographic regions [ 15 ]. They were also asked to report on the speciality in which supervision took place as research in post-graduate medical education has found differences in psychological safety between specialities [ 14 , 16 ].…”
Section: Methodsmentioning
confidence: 99%